Inverse Relationship between the Inflammatory Marker Pentraxin-3, Fat Body Mass, and Abdominal Obesity in End-Stage Renal Disease - Miyamoto, Tetsu (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: Pentraxin-3 (PTX3) belongs to the same pentraxin superfamily of acute-phase reactants as C-reactive protein (CRP). Abdominal fat accumulation in ESRD is considered a chronic inflammatory state, but the relationship of PTX3 to this phenomenon is unknown. This study assesses plausible associations between PTX3 and surrogates of fat mass deposits in dialysis patients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Circulating levels of PTX3, CRP, and IL-6 were cross-sectionally analyzed in relation to anthropometric and nutritional surrogate markers of fat tissue in two cohorts comprising 156 prevalent hemodialysis (HD) and 216 incident dialysis patients. RESULTS: In both cohorts, PTX3 was negatively associated with body mass index (BMI) and fat body mass index (FBMI) derived from anthropometrics and leptin, whereas there was a positive association with adiponectin. In prevalent HD patients, those with larger waist circumference (above gender-specific median values) had lower PTX3, higher CRP, and higher IL-6 levels. This was also true in multivariate analyses. In both cohorts, multivariate regression analyses showed that PTX3 was negatively and CRP (or IL-6) was positively associated with FBMI. CONCLUSIONS: Although CRP and IL-6 were directly associated with body fat, PTX3 levels showed negative correlations with surrogates of adipose tissue in two independent cohorts of ESRD patients. Understanding the underlying reasons behind these opposite associations may have clinical relevance given the survival advantage described for obese patients on dialysis.